Subjective perception of selected phenomena in the Czech language - Bednaříková, Božena; Grabovská Žvaková, Kateřina (Bohemistyka, 2025)
The case study focuses on the subjectively perceived challenges of learning Czech as a foreign language in an academic environment, especially in practically oriented courses. The study is comparative in nature. It uses a questionnaire survey to investigate the attitudes of two groups of students towards their specific views on preformulated statements concerning (1) their overall perception of Czech, (2) selected issues of Czech language acquisition, and (3) some grammatical rules. Despite its subjective nature based solely on the students’ feelings and impressions, the study can contribute to the learning process by providing insight into their opinions and perspectives after taking a two-semester Czech course, the main goal of which is to familiarize students with the language and provide them with a so-called survival course. Understanding their perspectives can enable educators to adapt language teaching more effectively. It is particularly positive that students see the possibility of reaching a communicative level in the not too distant future, despite the problems that learning Czech brings.